HUBUNGAN ANTARA TINGKAT PENGETAHUAN DENGAN TINGKAT KEPATUHAN DALAM MENGGUNAKAN ALAT PELINDUNG DIRI PADA PETANI PENGGUNA PESTISIDA - I Dewa Ayu Agung Inten Darmayanti; Ketut Tirta yasa; I Kadek Saputra (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2015)
Abstract. Demands for improved quality and food quality resulted in pesticide use can not be avoided. Uncontrolled use of pesticides causes intoxication or poisoning problem is getting out of control. Pesticide poisoning should be able to be avoided by the use of appropriate APD comply. One of the originator factor of the compliance is knowledge that is very important domain for a person's actions. This study aims to determine the relationship between the level of knowledge with the level of compliance in the use of APD at farmer pesticide users in a Region Subak Kendran Village year 2015. This study used a descriptive correlational design with a